PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - SE, Erika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The study aims to reveal the influence of corporate governance and profitability on corporate social responsibility disclosure. The type of data used is secondary data. The population in this study is manufacturing company basic industry and chemical sector listed in the Indonesia Stocks Exchange in 2014 and 2015. The sampling method used is purposive sampling and obtained 114 sample. The data analysis method used in this study is multiple regression. The results of the study show that the mechanisms of corporate governance such as size board of commisioner and frequency o f board meeting have positive effect on the company’s disclosure upon it’s corporate social responsibility. While profitability with Return on Assets as the proxy have negative effect on corporate social responsibility disclosure. Meanwhile, the component of mechanisms of corporate governance such as independent board of commisioner, public shareholding and foreign ownership does not affect the corporate social responsibility disclosure.Keyword: Corporate Governance, Profitability, Corporate Social Responsibility Disclosure